Uji Kinerja Mesin Pemotong Adonan Kerupuk Otomatis dengan Pengaturan Ketebalan Potongan - Irma Fahrizal; Feby Nopriandy; Suhendra (Proklamasi 45 University, 2024)
The main problem cracker businesses face is the process of cutting cracker dough. Cutting crackers is currently done using a simple cutting tool, but the disadvantages are low cutting capacity, requiring much energy in operation, and low uniformity of cut results. An effort to overcome these problems is to conduct research by developing a cracker dough-cutting machine. The purpose of this research was to test the performance of an automatic cracker dough cutting machine. The independent variables are dough container motion and piece thickness, while the independent variables are piece capacity, piece uniformity, and percentage of damaged pieces. The dough container motion was varied into four treatments, namely 15, 17, 20, and 24 movements/minute. The dough piece thickness was varied into three 1, 2, and 3 mm treatments. Increasing the dough container movement per minute can significantly increase the capacity and percentage of piece damage. The largest capacity was achieved in treating 2 mm thick pieces with 24 dough container movements/minute, resulting in 2,004 pieces/hour. The uniformity of the best-cut results in the 3 mm thick cut with a value of 92.84%. The smallest percentage of piece damage is obtained in the treatment of 1 mm thick pieces with a dough container motion of 15 movements/minute, resulting in a damage percentage of 15.91%.